Randomized placebo-controlled trial of the effects of aspirin on dementia and cognitive decline. (21st July 2020) - Ryan, Joanne; Storey, Elsdon; Murray, Anne M.; Woods, Robyn L.; Wolfe, Rory; Reid, Christopher M.; Nelson, Mark R.; Chong, Trevor T.J.; Williamson, Jeff D.; Ward, Stephanie A.; Lockery, Jessica E.; Orchard, Suzanne G.; et al.
Abstract : Objective: To determine the effect of low-dose aspirin vs placebo on incident all-cause dementia, incident Alzheimer disease (AD), mild cognitive impairment (MCI), and cognitive decline in older individuals. Methods: Aspirin in Reducing Events in the Elderly (ASPREE) was a double-blind, placebo-controlled trial of low-dose aspirin. In the United States and Australia, community-dwelling individuals aged ≥70 years (US minorities ≥65 years) and free of cardiovascular disease, physical disability, and diagnosed dementia were enrolled. Participants were randomized 1:1–100 mg daily aspirin or placebo. The Modified Mini-Mental State Examination, Hopkins Verbal Learning Test–Revised, Symbol Digit Modalities Test, and Controlled Oral Word Association Test assessed cognition at baseline and over follow-up. Additional cognitive testing was performed in participants with suspected dementia ("trigger") based on within-study assessments or clinical history. Dementia was adjudicated according to DSM-IV criteria. National Institute on Aging–Alzheimer's Association criteria were used for AD and MCI subclassification. Results: A total of 19, 114 participants were followed over a median 4.7 years and 964 triggered further dementia assessments. There were 575 adjudicated dementia cases, and 41% were classified as clinically probable AD. There was no substantial difference in the risk of all dementia triggers (hazard ratio [HR], 1.03; 95% confidence interval [CI], 0.91–1.17), probable AD (HR, 0.96; 95% CI, 0.74–1.24), or MCI (HR, 1.12; 95% CI, 0.92–1.37) between aspirin and placebo. Cognitive change over time was similar in the aspirin and placebo groups. Conclusions: There was no evidence that aspirin was effective in reducing risk of dementia, MCI, or cognitive decline. Follow-up of these outcomes after initial exposure is ongoing. Classification of evidence: This study provides Class II evidence that for healthy older individuals, low-dose aspirin does not significantly reduce the incidence of dementia, probable AD, MCI, or cognitive decline. Clinicaltrials.gov identifier: NCT01038583.